Efeito das variáveis abióticas na produção primária de Egeria najas e Utricularia breviscapa da lagoa do Óleo (Estação Ecológica de Jataí, Luiz Antônio - SP) - Petracco, Paula (2006)
This study was developed at Oleo lagoon, an oxbow sited on Mogi Guaçu river floodplain, located in Estação Ecológica de Jataí (Luís Antônio SP Brazil). To evaluate the river level fluctuation on the metabolism of this lagoon the following activities were done: i) limnological inventories (pH, dissolved oxygen, ammonium, total nitrogen, total phosphorus, iron, magnesium, sodium, potassium, organic carbon, inorganic carbon, suspended matter, temperature, electrical conductivity and photosynthetic active radiation); ii) the lagoon batimetry; iii) in situ incubations to evaluate the primary production rates of two species of submerged aquatic macrophytes (Egeria najas Planchon and Utricularia breviscapa Wright ex Griseb); iv) simulation of levels of river overflow. In the rainy season, due to overflow of the waters of Mogi Guaçu river into the lagoon, intense modifications of abiotic variables were verified. In the dry period, when the lower values of temperature, electrical conductivity, total suspended matter, vertical light extinction coefficient, total carbon concentrations, NTK and Ptotal occurred, the E. najas stands were located in the bottom of the lagoon and the photosynthetic rates were significantly higher than in the rainy period, and the light was the main variable controlling this process. For U. breviscapa, the photosynthetic rates were higher in the rainy season, presenting possible relation to the values of temperature and inorganic carbon concentrations, which were higher in this period. From the results, it was observed that Oleo Lagoon showed three different limnological phases: dry, rainy without overflow and rainy with overflow. Considering it is a oxbow lake situated in a conservation unit, the change in limnological and biochemical characteristics were due to the overflow pulse, influencing directly or indirectly the primary production of E. najas and U. breviscapa.